2012
DOI: 10.5424/fs/2012213-02895
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhization of containerized Pinus nigra seedlings with Suillus granulatus under open field conditions

Abstract: Seedling mycorrhization acts as an efficient tool for improving the quality of seedlings. In this study, the effectiveness of Suillus granulatus, originating from Pinus heldreichii forests (Montenegro), to produce containerized ectomycorrhizal seedlings of autochthonous Pinus nigra in open field conditions was investigated. Spore (10 6 , 10 7 , 10 8 ) and vegetative (1:16, 1:8, 1:4) inoculation on ectomycorrhizal formation and seedling growth were tested. Spore and vegetative inoculums of autochthonous Pisolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…It is of note that our qPCR estimators of ITS1 copy numbers aimed to test inoculum loads, but included likely a large proportion of non-EcM taxa as indicated by the presence of many non-EcM OTUs in the ectomycorrhizospheres. Further, the high colonization of the non-native pine suggests readily available and compatible inoculum, a result consistent with other studies that have shown P. nigra broad compatibility with cosmopolitan EcM fungi as well as species typically associated with members of Pinaceae or Fagaceae (Martin-Pinot et al 2006;Lazarevic et al 2012;Trocha et al 2012). Our high and rather stable colonization may relate to minimal soil disturbance near our urban mature trees, the adjacency of the two hosts at each of the sites, or the relatively adjacent undisturbed non-urban inoculum sources around the small urban center.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…It is of note that our qPCR estimators of ITS1 copy numbers aimed to test inoculum loads, but included likely a large proportion of non-EcM taxa as indicated by the presence of many non-EcM OTUs in the ectomycorrhizospheres. Further, the high colonization of the non-native pine suggests readily available and compatible inoculum, a result consistent with other studies that have shown P. nigra broad compatibility with cosmopolitan EcM fungi as well as species typically associated with members of Pinaceae or Fagaceae (Martin-Pinot et al 2006;Lazarevic et al 2012;Trocha et al 2012). Our high and rather stable colonization may relate to minimal soil disturbance near our urban mature trees, the adjacency of the two hosts at each of the sites, or the relatively adjacent undisturbed non-urban inoculum sources around the small urban center.…”
Section: Discussionsupporting
confidence: 77%
“…Pinus nigra (Austrian pine) is native to Mediterranean Europe but often chosen as an ornamental in Kansas and mixed with various Quercus spp. Although exotic to North America, inoculation and common garden studies show that P. nigra is broadly compatible with cosmopolitan EcM taxa (Martin-Pinot et al 2006) and share fungi with other Pinaceae (Lazarevic et al 2012) as well as Fagaceae (Trocha et al 2012). One isolated individual of each species was selected at each of the six urban sites for a total of twelve trees across the study (Table 1).…”
Section: Study Sitesmentioning
confidence: 99%
“…Kuntze, a common fungus often associated with this pine in the northern Sierra Nevada [15,21] and one long known to infect its root systems [22,23]. Mycorrhizal coloration and morphology here largely conformed to that documented for this symbiont specifically [23][24][25], but it was not possible to confirm its identity through its sporocarps, despite their unique appearance [26], because none were found in the seedling containers at any juncture of the study, although they occur seasonally at both of the field sites where the three soils were obtained and in the vicinity of the greenhouse where the study was conducted.…”
Section: Short Root and Mycorrhizal Formationmentioning
confidence: 85%
“…In Montenegrin and Serbian nurseries, controlled mycorrhizal inoculation of seedlings has yet to become a common practice, but positive experiences with mycorrhization of conifer seedlings by autochthonous fungal isolates from this region have been already known for conifers (Lazarević, 2010;Lazarević et al, 2012 ), also as in case of conifer and hardwood mycorhization with commercial products (Lazarević, 2009).…”
Section: Discussionmentioning
confidence: 99%